PENGGUNAAN DIKSI DAN GAYA BAHASA KONTEN VIDEO MOTIVASI MERRY RIANA DALAM MEDIA TIKTOK - Sari, Husnul Anita; Sofyan, Akhmad; Hariyadi, Edy; Asrumi, Asrumi; Suyanto, Budi (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2024)
Merry Riana's motivational video content contains encouragement to build an optimistic attitude when you experience failure in achieving your goals, are disappointed by your partner, receive negative comments from other people and when you want to choose a potential life partner. The purpose of this study is to describe the use of diction and motivational language style of Merry Riana in TikTok media using semantic and pragmatic studies. This research is a text-based descriptive qualitative research, using the referential equivalent method to analyze the meaning and using the interpretation method to reveal the purpose of motivation based on related contexts. The results of this study indicate that Merry Riana uses greeting diction, synonym diction, special diction, general diction, foreign language diction, borrowed word diction, popular diction, scientific diction and conversational diction. The diction that is widely used is the diction of a foreign language, namely English. The style of language found in this study uses a style of language based on sentence structure of 5 types and a style of language based on the direct or indirect meaning of 9 types. The style of language that is most widely used is the style of language based on whether the meaning is direct or not, namely, climax. The use of diction and language style functions to: 1) encourage listeners when they feel hopeless; (2) influencing and convincing the listeners with the motivational delivered; and (3) provide an interesting effect on motivational speech patterns.